Impacts of climate and season on water quality in aquaculture ponds - Sriyasak, Patcharawalai; Whangchai, Niwooti; Chitmanat, Chanagun; Promya, Jongkon; Lebel, Louis (Asia-Pacific Journal of Science and Technology, 2017)
Seasons, weather and climate affect aquaculture. This article reviews the impacts of climate and season on water quality and aquaticanimals, and speculates on the use of models to better understand aquaculture pond ecosystem dynamics. Findings underline how climate and season inflence water quality, including water temperature, dissolved oxygen and ammonia concentrations. These factors, in turn, affect growth, survival and risks ofdisease. Pond ecosystem models appear a promising tool to understand and possibly project how pond aquaculture may respond to climate variability and change, and thus, explore management options useful for maintaining suitable waterquality conditions.